2020
DOI: 10.1177/1557988320954022
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Male-Dominated Occupations

Abstract: Low levels of health literacy are associated with poorer health outcomes. Both individual- and social-level factors have been identified as predictors of low health literacy, and men are known to have lower health literacy than women. Previous research has reported that men working in male-dominated occupations are at higher risk of accidents, injury, and suicide than other population groups, yet no study to date has examined the effect of gendered occupational contexts on men’s health literacy. The current ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A number of European countries have reported that low education, old age, and financial scarcity are commonly associated with low health literacy [ 28 , 29 ]. However, information on the relationship between sex and health literacy is still lacking, and the results of health literacy according to sex suggest otherwise [ 30 , 31 ]. Individuals with IFG need health and food information they can understand and use in order to maintain target blood glucose levels and properly manage their health [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of European countries have reported that low education, old age, and financial scarcity are commonly associated with low health literacy [ 28 , 29 ]. However, information on the relationship between sex and health literacy is still lacking, and the results of health literacy according to sex suggest otherwise [ 30 , 31 ]. Individuals with IFG need health and food information they can understand and use in order to maintain target blood glucose levels and properly manage their health [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with IFG need health and food information they can understand and use in order to maintain target blood glucose levels and properly manage their health [ 32 ]. However, Koreans have a low understanding of food information and a low level of practice in using information for food selection [ 30 ]. In particular, middle-aged Korean male are less interested in food purchases [ 13 ], and married middle-aged female still take on the main responsibility for preparing meals at home and as food purchasers [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These elements may influence and contribute to recruitment efforts for men in the participation of workplace health promotion programming. Gender-based programming may be especially relevant for engaging men in male-dominated workplaces, where low levels of health literacy among men have been highlighted ( Milner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2016). Men in male-dominated industries are also at greater risk of poorer physical health and more likely to engage in health-harming behaviours (Milner et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…construction, transport and mining (Roche et al, 2016)) are particularly vulnerable to poor mental health, with higher rates of depression than the general population (Roche et al, 2016). Men in male-dominated industries are also at greater risk of poorer physical health and more likely to engage in health-harming behaviours (Milner et al, 2020). Research suggests these poor health outcomes and behaviours may be a consequence of traditional masculine norms such as self-sufficiency, emotional control, acting "tough" and risk-taking (Ragonese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%